Actions to halt biodiversity loss generally benefit the climate. (27th February 2022) - Shin, Yunne‐Jai; Midgley, Guy F.; Archer, Emma R. M.; Arneth, Almut; Barnes, David K. A.; Chan, Lena; Hashimoto, Shizuka; Hoegh‐Guldberg, Ove; Insarov, Gregory; Leadley, Paul; Levin, Lisa A.; Ngo, Hien T.; et al.
Abstract: The two most urgent and interlinked environmental challenges humanity faces are climate change and biodiversity loss. We are entering a pivotal decade for both the international biodiversity and climate change agendas with the sharpening of ambitious strategies and targets by the Convention on Biological Diversity and the United Nations Framework Convention on Climate Change. Within their respective Conventions, the biodiversity and climate interlinked challenges have largely been addressed separately. There is evidence that conservation actions that halt, slow or reverse biodiversity loss can simultaneously slow anthropogenic mediated climate change significantly. This review highlights conservation actions which have the largest potential for mitigation of climate change. We note that conservation actions have mainly synergistic benefits and few antagonistic trade‐offs with climate change mitigation. Specifically, we identify direct co‐benefits in 14 out of the 21 action targets of the draft post‐2020 global biodiversity framework of the Convention on Biological Diversity, notwithstanding the many indirect links that can also support both biodiversity conservation and climate change mitigation. These relationships are context and scale‐dependent; therefore, we showcase examples of local biodiversity conservation actions that can be incentivized, guided and prioritized by global objectives and targets. The close interlinkages between biodiversity, climate change mitigation, other nature's contributions to people and good quality of life are seldom as integrated as they should be in management and policy. This review aims to re‐emphasize the vital relationships between biodiversity conservation actions and climate change mitigation in a timely manner, in support to major Conferences of Parties that are about to negotiate strategic frameworks and international goals for the decades to come. Abstract : This review provides evidence that biodiversity conservation actions have mostly synergistic benefits and few antagonistic trade‐offs with climate change mitigation. Specifically, we identify co‐benefits in 14 out of the 21 action targets of the draft post‐2020 global biodiversity framework of the Convention on Biological Diversity. These relationships are context‐ and scale‐dependent; therefore, based on 12 case studies in different parts of the world, we showcase local biodiversity conservation actions that can be incentivized, guided and prioritized by global objectives and targets. We highlight the close interlinkages between biodiversity, climate change mitigation, other nature's contributions to people and good quality of life which need to be better integrated in management and policy.